LEXICAL AND STYLISTIC FEATURES OF TRANSLATION OF A LITERARY TEXT INTO GERMAN (BASED ON THE WORKS OF SERHIY ZHADAN) - ЛИСЕЦЬКА, Наталія; КАРПЕВИЧ, Альона (Current Issues of Foreign Philology, 2024)
The article examines the lexical and stylistic features of translation of a literary text into German on the example of The Orphanage: A Novel by Serhiy Zhadan. The concept of literary translation, its features and main requirements that the translator must adhere to during the translation process are considered. It has been established that literary translation is not only a direct transmission of a text into a foreign language, but also a tool of cultural exploration of the world, a factor of a certain culture. The author’s style was analyzed and it was determined that the writer uses a number of figurative and tropic means, such as epithet, simile, metaphor, allegory, and symbol. It was established that the author turns to the stylistic technique of irony and color symbolism. The use of different shades of dark colors from black to gray and dark blue symbolizes the situation of devastation and helplessness in the region where the main character lives. When comparing the original source and its German-language version, it was noted which translation transformations the translators resort to. It has been observed that at the morphological level, the performers are most often inclined to the means of creating a composite, which is typical for the target language. The most frequent options are “noun plus noun”, “adjective plus noun”. In order to preserve the meaning or clarify the connotation of certain language units, the method of generalization, transformation, and logization is used. At the syntactic level, the original text often contains complex subordinate clauses, as well as sentences complicated by adjectival and participial phrases. When translating such cases, performers use the method of omitting and replacing a complex sentence with a simple one. During the research, certain differences in the translation were revealed, since the structure of the Ukrainian and German languages is different, it is impossible to always preserve the original constructions. It was concluded that the translators, skillfully applying translation transformations, managed to convey the author’s idea to the reader and not violate the aesthetic integrity of the original.